Perspectives on church and mission: The missional church and metaphors for the church - Pieter Verster (Verbum et Ecclesia, 2022)
The most important issues for the missional church should be to establish the relation between mission and the church. The methodology used is to listen to voices concerning relevant issues in the missional church. Many important aspects of the missional church are discussed to give an overview of contemporary challenges. Metaphors for the church, such as people of God, body of Christ, temple of God, bride of Christ and witness of God give many essential guidelines for how the church should engage the world. By evaluating these metaphors, new suggestions can be made. It is concluded that the church should always be the church of the living Christ, living new lives in this world with the eye on the world to come.